ANALYSIS OF CONSUMER RESPONSE TO MARKETING MIX STRATEGY AT FAJAR FARMA PHARMACY SAMARINDA - Novia Saputri; Siti Jubaidah; Achmad Kadri Ansyori (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
Pharmacies are a form of health service facility for the community, with the rapidly increasing number of pharmacies having a positive impact on the community, that is being able to compare prices from one pharmacy to another so that each pharmacy can provide better services at competitive prices. Competition for pharmacies, whether privately or publicly owned, is becoming more common. This makes the pharmacy business more competitive, including Fajar Farma Pharmacy. The purpose of the study was to determine the 7P marketing mix strategy applied at Fajar Farma Pharmacy and the relationship between the 7P marketing mix strategy and consumer satisfaction at Fajar Farma Pharmacy. The sample in this research was consumers who buy drugs at Fajar Farma Pharmacy. The sampling method used was non-probability sampling, namely purposive sampling. The independent variable in this study is the marketing mix strategy, which consists of product, price, place, promotion, people, process, and physical evidence, and the dependent variable in this study is customer satisfaction with services. In this study, data analysis was done using a descriptive method, which means that no conclusions or generalizations are made. Inferential statistics were used in analyzing a sample of data so that the results can be applied to the population. Based on the results of research obtained from 350 respondents, the marketing mix strategy applied at Fajar Farma Pharmacy has gone very well. This is in line with the results of the average value obtained in the aspects of product, price, place, promotion, people, process, and physical evidence, which are all in the